Aluminum-copper alloy anode materials for high-energy aqueous aluminum batteries - Ran, Qing; Shi, Hang; Meng, Huan; Zeng, Shu-Pei; Wan, Wu-Bin; Zhang, Wei; Wen, Zi; Lang, Xing-You; Jiang, Qing (Nature communications, 2022)
Aqueous aluminum batteries are promising post-lithium battery technologies for large-scale energy storage applications because of the raw materials abundance, low costs, safety and high theoretical capacity. However, their development is hindered by the unsatisfactory electrochemical behaviour of the Al metal electrode due to the presence of an oxide layer and hydrogen side reaction. To circumvent these issues, we report aluminum-copper alloy lamellar heterostructures as anode active materials. These alloys improve the Al-ion electrochemical reversibility (e.g., achieving dendrite-free Al deposition during stripping/plating cycles) by using periodic galvanic couplings of alternating anodic α-aluminum and cathodic intermetallic Al 2 Cu nanometric lamellas. In symmetric cell configuration with a low oxygen concentration (i.e., 0.13 mg L −1 ) aqueous electrolyte solution, the lamella-nanostructured eutectic Al 82 Cu 18 alloy electrode allows Al stripping/plating for 2000 h with an overpotential lower than ±53 mV. When the Al 82 Cu 18 anode is tested in combination with an Al x MnO 2 cathode material, the aqueous full cell delivers specific energy of ~670 Wh kg −1 at 100 mA g −1 and an initial discharge capacity of ~400 mAh g −1 at 500 mA g −1 with a capacity retention of 83% after 400 cycles. Aqueous Al-ion batteries are attractive post-lithium battery technologies. Here Al-Cu alloy lamellar heterostructures with periodic galvanic couplings are reported as efficient anode active material to produce high-energy aqueous Al-ion batteries.